Lignin as an Additive for Advanced Composites - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Lignin, an abundant renewable resource material next to cellulose, can be one of the most essential bio-resources as a raw material for the production of environmentally friendly polymers and polymer composites. Due to its chemical structure, lignin can provide additional functionalities in composites. It can be used as reinforcers, fillers, compatibilizers and even stabilizing agents in polymer composites. In this chapter use of lignin in composites, its additional benefits and possible applications were summarized. Structure-process-property relations were particularly emphasized. Because of the aromatic structure and multifunctional side groups, lignin can be a promising, environmentally friendly additive as a free radical scavenger which prevents oxidation reactions. For the structural composite applications, material properties were found to be highly dependent on process conditions. One can observe controversy in the reported mechanical properties of composites with similar components and similar lignin concentrations. Thus in some studies addition of lignin resulted with enhanced strength and modulus; while lignin just acted as a filler in some others. Those studies should be carefully evaluated considering the process conditions. Further improvements can also be achieved after modifying lignin chemically.
Keywords: Lignin; Biocomposites; Additive; Compatibilizer; Filler; THERMOPLASTIC-LIGNOCELLULOSE COMPOSITES; TREATED ALCELL LIGNIN; POLYPROPYLENE COMPOSITES; ANTIOXIDANT PROPERTIES; MECHANICAL-PROPERTIES; POLYMER COMPOSITES; TECHNICAL LIGNINS; KRAFT LIGNIN; CELLULOSE; WOOD